2022
DOI: 10.3390/children9071010
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Prognostic Factors in MRI during Spica Cast Therapy Treating Developmental Hip Dysplasia with Midterm Follow-Up

Abstract: Closed reduction followed by spica casting is a conservative treatment for developmental dysplasia of the hip (DDH). Magnetic resonance imaging (MRI) can verify proper closed reduction of the dysplastic hip. Our aim was to find prognostic factors in the first MRI to predict the possible outcome of the initial treatment success by means of ultrasound monitoring according to Graf and the further development of the hip dysplasia or risk of recurrence in the radiological follow-up examinations. A total of 48 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In some studies, the treatment goal was defined as an α angle more than 64°. 18 , 39 Some authors argued rounding or blunt acetabular rim might affect the measurement of the α angle and influence the treatment strategy. 40 42 Hareendranathan et al 42 proposed a contour-based α angle and a rounding index to improve the reliability and accuracy of DDH diagnosis, and they found that the apex point moved 8 mm leading to a 10° change of α angle.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the treatment goal was defined as an α angle more than 64°. 18 , 39 Some authors argued rounding or blunt acetabular rim might affect the measurement of the α angle and influence the treatment strategy. 40 42 Hareendranathan et al 42 proposed a contour-based α angle and a rounding index to improve the reliability and accuracy of DDH diagnosis, and they found that the apex point moved 8 mm leading to a 10° change of α angle.…”
Section: Discussionmentioning
confidence: 99%
“…Hip joint dysplasia cannot be excluded with certainty by inconspicuous ultrasound findings in infancy imately 20-40% of all cases of adult hip osteoarthritis are due to unrecognized or untreated DDH [1]. Postnatal infant examination at 3-8 weeks detected in early childhood, it can be often addressed with non-surgical methods of splinting [8]. In skeletally mature patients, reorientation osteotomy represents the gold standard for treatment of the underlying pathomorphology.…”
Section: Ca 50% Of Patients Of Patients With Hip Dysplasia In Adultho...mentioning
confidence: 99%
“…11 MRI is advantageous in terms of the nonexposure of sensitive developing tissues to ionizing radiation and providing more information about the soft tissues in and around the hip joint and the cartilaginous epiphysis. 12 Moreover, the fast sequence MRI can be performed in patients with spica cast and does not require sedation or anesthesia, although the mean study time of ultrafast MRI was 6 ± 1 minute. 13 Ultrasonography is a noninvasive examination method that does not involve radiation exposure and can provide detailed imaging of the cartilage and soft tissues.…”
mentioning
confidence: 99%
“…The sensitivity and specificity of CT and MRI for the detection of hip dislocation in the spica cast have been found to be equivalent 11 . MRI is advantageous in terms of the nonexposure of sensitive developing tissues to ionizing radiation and providing more information about the soft tissues in and around the hip joint and the cartilaginous epiphysis 12 . Moreover, the fast sequence MRI can be performed in patients with spica cast and does not require sedation or anesthesia, although the mean study time of ultrafast MRI was 6 ± 1 minute 13 .…”
mentioning
confidence: 99%